On-line extraction and determination of carbofuran in raw milk by direct HPLC injection on an ISRP column - Menezes, Manoel Lima de [UNESP]; Felix, G.; Demarchi, ACCO (Vieweg, 1998)
A method has been developed for extraction and determination of carbofuran in milk. The method involved direct injection of raw milk on to a human serum albumin dimethyloctyl-silica gel (HSA-Cs) column and the use of 80:20 (v/v) 0.01 M phosphate buffer pH 5.5 - acetonitrile as mobile phase. UV spectrophotometric detection was performed at 220 nm. Identification was based on retention time. Quantification was performed by automatic peak-area determination and was calibrated by use of an external standard.
Keywords: column liquid chromatography; carbofuran pesticides; on-line analysis of milk